The role of cervical muscles in mitigating concussion. Issue 6 (June 2019) - Eckersley, Christopher P.; Nightingale, Roger W.; Luck, Jason F.; Bass, Cameron R.
Abstract: Objectives: Increased neck strength has been hypothesized to lower sports related concussion risk, but lacks experimental evidence. The goal is to investigate the role cervical muscle strength plays in blunt impact head kinematics and the biofidelity of common experimental neck conditions. We hypothesize head kinematics do not vary with neck activation due to low short term human head-to-neck coupling; because of the lack of coupling, free-head experimental conditions have higher biofidelity than Hybrid III necks. Methods: Impacts were modeled using the Duke University Head and Neck Model. Four impact types were simulated with six neck conditions at eight impact positions. Peak resultant linear acceleration, peak resultant angular acceleration, Head Injury Criterion, and Head Impact Power compared concussion risk. To determine significance, maximum metric difference between activation states were compared to critical effect sizes (literature derived differences between mild and severe impact metrics). Results: Maximum differences between activation conditions did not exceed critical effect sizes. Kinematic differences from impact location and strength can be ten times cervical muscle activation differences. Hybrid III and free-head linear acceleration metrics were 6 ± 1.0% lower and 12 ± 1.5% higher than relaxed condition respectively. Hybrid III and free-head angular acceleration metrics were 12 ± 4.0% higher and 2 ± 2.7% lower than relaxed condition respectively. Conclusions: Results from a validated neck model suggest increased cervical muscle force does not influence short term (<50 ms) head kinematics in four athletically relevant scenarios. Impact location and magnitude influence head kinematics more than cervical muscle state. Biofidelic limitations of both Hybrid III and free-head experimental conditions must be considered.